Penerapan Metode SAW Dalam Menentukan Juara Lomba Kategori Vocal Group Di LPPN - Charolina, Yanthi; Honni, Honni; Andry, Yohannes Fernandes (Universitas Nusantara PGRI Kediri, 2023)
The history of vocal music is very old. Even some experts believe that humans have started singing before they began to communicate with modern languages. Popular vocal music as we know it today is rooted in the traditions of European society in the Middle Ages. It was only the middle ages that everything progressed in a more modern direction. A decision support system (DSS) is a part of a computer-based information system that is used to support decision making in determining the best alternative within a particular company or organization and can also be used to rank in determining championships when carrying out various competitions. In this study, the authors used the SAW method to determine championships in vocal group activities held by the National PESPARAWI Development Institute (LPPN). This SAW method is the SAW method which is one of the best methods for ranking based on the different attributes and weights of each participant so that the results are more effective